Teknik Pangkas Akar untuk Meningkatkan Produksi Bibit Melinjo Bermikoriza - Arum Sekar Wulandari; . Supriyanto (Institut Pertanian Bogor, 2013)
Mycorrhizal symbiosis is the result of mutualistic interactions between plants and fungi. Melinjo (Gnetum gnemon) naturally associate with ectomycorrhizal Scleroderma sinnamariense and Scleroderma sp. fungi. Artificial inoculation can be applied to young seedlings (1-2 months old), before the roots contain woody material. The purpose of this study was to apply the root pruning techniques to improve gnetum mycorrhizal seedlings production. The study was conducted in a greenhouse using 7 months old seedlings. The treatments consisted of 3 root pruning levels (0, 30, and 50%) and ectomycorrhizal fungi inoculum (control, mycorrhizal seedlings, and soil inoculum). Observations were carried out for 4 months to the seedling growth and root colonization by ectomycorrhizal fungi. Height, diameter, and biomass of melinjo seedlings in all treatments were not significantly different. Thus, root pruning activities do not affect the growth of seedlings. Artificial inoculation produce mycorrhizal seedlings, whereas controls were uninfected. Root pruning increased number of root branching. Root pruning at level 50% increased mycorrhizal seedlings production, but the percentage of root colonization was not significantly difefernt at all pruning levels.